Quantitative Proteomic Profile of Psoriatic Epidermis Identifies OAS2 as a Novel Biomarker for Disease Activity - Zhou, Yuan; Wang, Ping; Yan, Bing-Xi; Chen, Xue-Yan; Landeck, Lilla; Wang, Zhao-Yuan; Li, Xin-Xin; Zhang, Jing; Zheng, Min; Man, Xiao-Yong (Frontiers in Immunology, 2020)
Psoriasis is a common chronic inflammatory systemic disease. Epidermal proteins are considered to be important in maintaining skin barrier function, innate immunity and inflammation. To define more possible roles of the epidermis in the pathogenesis of psoriasis, quantified proteomic analysis was used to screen and analyze the differentially expressed epidermal proteins between 16 psoriasis patients and 15 healthy controls. Upregulated differential expression proteins (DEPs) include several significant functional protein clusters, including antimicriobial peptides (AMPs) and antiviral proteins (AVPs). The levels of 2-5-oligoadenylate synthase 2 (OAS2) in both epidermis and serum levels were significantly elevated in psoriasis, also positively corelated with Psoriasis Area Severity Index (PASI) scores and Body Surface Area (BSA) scores. Moreover, OAS2 expression in psoriatic skin significantly decreased after IL-17R mono-antibody treatment. It is clarified that inflamed keratinocytes were the main source of abnormally increased OAS2 in psoriasis skin by immunofluorescence and primary cell cultures. Keratinocyte-derived OAS2 can be induced by not only IFNβ, but also psoriasis associated cytokines like IL-17A and IL-6. This study revealed AMPs and AVPs are two important functional protein clusters altering innate immune in psoriatic epidermis. OAS2 is a novel potential sensitive biomarker, that could predict the severity and activity of psoriasis, and also could be used as an indicator to evaluate or monitor the efficacy of clinical treatment.